Preparation and Properties of Nanosized Fluorescent Solid Films Based on a Polyelectrolyte–Surfactant Complex with Organic Dyes - Seliverstova, E.V.; Ibrayev, N.Kh.; Kudaibergenov, S.E. (Springer, 2013)
A procedure for preparing an organosoluble stoichiometric complex based on a cationic polyelectrolyte and an anionic surfactant is described. A method is proposed for forming monolayers at the water-air interface, along with conditions for preparing fluorescent nanosized solid films based on polyelectrolyte complex and organic dyes using the Langmuir-Blodgett (LB) method. The spectral and luminescent properties of the obtained films are investigated. It is established from the absorption and fluorescence spectra of LB films that electrostatic interaction between the molecules of polyelectrolyte complex and oxazine dyes results in dimer formation.